Factors That Influence People's Interest In Using Sharia Banking Products - Abdul Nasser Hasibuan; Ali Hardana (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2024)
Financial Literacy is knowledge, skills and beliefs that influence attitudes and behavior aimed at achieving prosperity by being financially intelligent in management and decision making. Based on observations made by researchers of the people of Tano Tombangan Angkola District, several problems were found, including lack of understanding, awareness of saving and very poor financial management with the high level of consumption of the people of Tano Tombangan, Angkola District, being one of the problems. The aim of this research is to determine the influence of financial literacy and digital marketing on people's interest in using sharia banking products. This research is quantitative research using primary data. The data collection technique used was a questionnaire. Sampling in this study used the Accidental Sampling technique with a sample size of 94 people determined using the Taro Yamane formula. The data analysis methods used are normality test, multicollinearity test, heteroscedasticity test, coefficient of determination test, multiple linear regression test, t test and F test. The t test results show that there is an influence of Financial Literacy and Digital Marketing on Community Interest in Using Sharia Bank Products (Case Study in Tano Tombangan Angkola District). Hopefully this research will contribute to banks in increasing their customers.